Analysis of Receivables Management to Minimize Bad Debts at Go Vacation Indonesia - N L R Yuliasari; I K Suandi; I G A O Sudiadnyani (Jurusan Akuntansi Politeknik Negeri Bali, 2019)
This study aimed to describe 1) credit analysis in Go Vacation Indonesia 2) assessment of management of receivable accounts in Go Vacation Indonesia 3) management of receivable accounts to minimize bad debts in Go Vacation Indonesia. The data that was used for this study were aging account receivable schedule, credit sales data, credit standards, and receivable accounts policy. The measuring instruments that was used to carry out this research were 5C analysis to analyze the standard credit facility, assess the management of receivables which included billing and collecting of receivables policies to analyze compliance with policies and ratios related to receivable accounts to evaluate management of receivable accounts, management of receivable accounts minimized bad debts to minimize bad debt expenses. The results of the study showed that the 5C analysis for credit facility granting standards had fulfilled the requirements. Billing and collecting receivables were not effective yet because they did not appropriate with the policy. The results of the ratio of receivable accounts were not optimal. Bad debt expenses that could be minimized in 2016 was Rp59,893,531, in 2017 was Rp80,185,316, in 2018 was Rp69,989,977.